Development and Assessment of a Coping Scale for Infertile Women in Turkey - ÜNSAL, GÜL (WOMENS HEALTH & ACTION RESEARCH CENTRE, 2018)
Infertile women feel more psychological stress and pressure than their husbands, and the prevalence of anxiety and depression among them are higher. This study aimed to develop a culture-specific measurement tool to identify the strategies of infertile women in dealing with infertility-related problems. This was a scale development study. This study was carried out in three different fertility centers in the three largest cities in Turkey. The data were collected using personal information form and through the application of a Coping Scale for Infertile Women (CSIW) protocol. Ways of Coping with Stress Inventory. Cronbach's alpha, Intraclass Correlation Coefficient and Spearman` s Rank correlation analyses were used to determine the reliability of the scale. The results of explanatory factor analysis and a factor structure of the Coping Scale for Infertile Women, comprising 50 items, were examined, and the data were determined to be suitable to perform factor analysis. The internal consistency of the scale was found to be 0.880. The number of factors in the scale was 10, and the internal consistency of the factors was 0.720. The results showed that the CSIW had good reliability and validity.
Keywords: Infertility; Women; Coping; Scale development; SPIRITUALITY; COUPLES; STYLES